Security Attacks and Challenges of Wireless Sensor Network’s -a Review - Shaik, Riaz; Shakeel Ahamad, Shaik (International Journal of Engineering and Technology, 2018)
Wireless sensor networks are becoming part of many of the research areas to address different issues related to technological and societal. So, The developments in wireless communication technology have made the deployment ofÂ wireless sensor nodes connected through wireless medium, known as wireless sensor networks. Wireless sensor networks have numerous applications in many fields like military , environmental monitoring , health , industry etc.. wireless sensor networks have more benefits over Wired networks .Though there are several advantages of wireless networks, they are prone to security issues. . Security became a major concern for wireless sensor networks because of the wider application. So ,this paper addresses the critical security issues of wireless sensor networks that may encounter in the different layers of the communication protocols like OSI.This paper presents a detailed review on the security issues and its challenges of the wireless sensor networks. Â Â